PEMBUATAN ALAT PENGERING KERUPUK UNTUK INDUSTRI KECIL PEDESAAN - Wibowo, Heri; Purnomo, Edy (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
The problems   faced  by crisply  industry  "Sarinah"   was  the  problem of dryer of kerecek (raw  crisply)  which  need wide of place and very depend on  weather.   The   operation    could   be  adapted   by  requirement    of   good production   on  noon   or  night.   Target   activity   of  this  program   was  give additional   aid  of  equipment   of  production   matching   with  requirement    of small  industry   so  that   production   mount   and  have  technology    mainstay production,  efficient  and cheap  of operating  expenses.To  overcome    problems    of  production   draining   of  crisply,   gone through the following  stages:   (1) making  scheme  of crisply  dryer  according to  requirement   of  small  industry;   (2)  making  crisply  dryer  with  adequate capacities  (15.000-20.000)    in a short  times  (7 -  8 hours),  and  (3)  partner industry can exploit  dryer technology  in an optimal  flashing.Execution  of activity  orients  on efficacy  of making  of dryer  able  tobe exploited  properly.  The result  of make-up  of small industrial  productivity after wearing  this appliance  is marked  with attainment  of larger  ones  om set. Total the omset  before  this  program  is 8000 crisply  sold (equivalent   of Rp800.000,00/day).   After  adjustment   of technology  of dryer,  tired  mean  omset13.000 until  15.000 crisply.  On bad weather,  industrial  this crisply  produces crisply  till  20.000   because   getting   the  order  5000  of  crisply   from  other industries.   This  means   program   of  this  voucher   can  increase   product   on small industry.Key words: dryer, crisply, small industrial